Long-Term Aortic Remodeling After Thoracic Endovascular Aortic Repair of Acute, Subacute, and Chronic Type B Dissections - Li, Zhenjiang; Wang, Xiaohui; He, Yangyan; Xiang, Yilang; Wu, Ziheng; Zhang, Hongkun; Li, Donglin (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aimed to investigate the characteristics and predictors of aortic remodeling over a long-term follow-up period after thoracic endovascular aortic repair (TEVAR) for acute, subacute, and chronic type B aortic dissection (TBAD). Methods: Patients who underwent TEVAR for TBAD from July 2011 to December 2013 were included, and relevant data were retrospectively analyzed. Results: After TEVAR, the true lumen (TL) dimension increased and the false lumen (FL) dimension decreased or did not change over a 5-year follow-up period in all three temporal groups. The proportion of thoracic aorta shrinkage was the highest in the subacute group (acute, 28.1%; subacute, 39.1%; chronic, 17.4%; P = 0.048), while abdominal expansion showed no significant difference among the groups (acute, 29.6%; subacute, 40.5%; chronic, 44.4%; P = 0.502). The chronic group had a lower rate of complete FL regression than that of the subacute or acute group at all anatomic sections, with significant differences only in the stented section (chronic, 21.7%; acute, 92.2%; subacute, 80.4%; P < 0.05) and the distal thoracic aortic section (chronic, 13.0%; acute, 31.1%; subacute, 50.0%; P < 0.05). Logistic regression analysis demonstrated that chronic dissection, TL compression, endoleak, number of branches from FL, and number of residual tears affected optimal FL remodeling. Conclusions: The present study provides data on aortic remodeling of TBAD after TEVAR during a long-term follow-up period. The features and risk factors of aortic remodeling are different in acute, subacute, and chronic phases at different aortic segments. These findings may have implications on timing for TEVAR.